KONTRIBUSI TATA TERTIB SEKOLAH TERHADAP PRESTASI BELAJAR PKN SISWA PADA SMP NEGERI 1 BAJENG KABUPATEN GOWA - Imam Suyitno; Mulyadi Rasyid (Universitas Negeri Makassar, 2018)
This study aims to determine: (1) The contribution of school discipline and academic achievement Civics students at SMP Negeri 1 Bajeng Gowa, (2) constraints faced by the school in enforcing the regulations, (3) Efforts carried out by the school in enforcing the school rules in SMP Negeri 1 Bajeng Gowa. This research is quantitative descriptive with population of all students in grade VIII SMP Negeri 1 Bajeng, totaling 150 students that do penerikan sample using purposive sampling techniques, and take parallel each class so that the total sample of 30 students and 2 teachers as informants the research consisted of teachers and teacher BK Civics. Data collection techniques used were questionnaires, interviews, and documentation, analysis of the data used is the product moment correlation test. From the analysis of hypothesis testing through correlation formula of Pearson Product Moment that no contribution the school rules on learning achievement Civics students at SMP Negeri 1 Bajeng Gowa, it is shown on the value of the correlation coefficient of 0.998 were consulted premises value at significance level α = 5% with the provision that if the calculated value> value table at significance level α = 5%, then the hypothesis is accepted, whereas if the calculated value <value table at significance level α = 5%, then the hypothesis is rejected. The results of the calculation table at significance level α = 5% yield calculated value = 0.998, while the value table for the calculated value = 0.361> table value then the hypothesis is accepted. This means that any contribution school discipline and academic achievement Civics students at SMP Negeri 1 Bajeng, while the constraints faced by the school in the enforcement of the order include: (1) cooperation between BK teachers with subject teachers and homeroom is not maximized, (2) the parents have not been too concerned about his son. In addition, as for the efforts taken by the school in the enforcement of the order include: (1) provide guidance, (2) establish cooperation with parents, (3) the provision of exemplary examples.